Coral Reefs, Convicts, Cadavers, Coffee Shops and Couture: Customizing Experiential Learning to Increase Comfort and Engagement - Grabowsky, Gail; Hargis, Jace; Davidson, Janet; Paynter, Allison; Suh, Junghwa; Wright, Claire (Journal of University Teaching and Learning Practice, 2017)
Experiential learning (EL) can offer a high impact educational opportunity that benefits students from diverse backgrounds, creating an inclusive learning environment. Barriers to the generalization of EL can include a lack of institutional support, risk avoidance, time, and faculty instructional ability. As well EL require additional efforts from students, which can include a non-traditional perspective of cognitive, psychomotor and affective domains. The authors have experienced success in optimizing three important EL components: preparation, customization and on-site triage. We report results from a quasi-experimental qualitative study of 102 students who responded to a post-event perception survey of their comfort levels, understanding, preparation and instructor’s role. We found that students were generally positive about their EL, however; most positive of the instructor helping them feel more comfortable during the EL (x̅=3.80 on a 4.00 scale) and their feelings afterward (x̅=3.75). Students were very positive in their belief that they learned more from the EL than in a traditional class (x̅=3.75). There were positive and significant changes in students attitudes, perceptions and beliefs in the time prior to the event compared to the time during and after. Students were significantly more likely to exhibit higher comfort levels after the event than prior (t =-3.459, p < .001).